2016
DOI: 10.1093/eurheartj/ehw413
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to ambient air pollution and traffic noise and incident hypertension in seven cohorts of the European study of cohorts for air pollution effects (ESCAPE)

Abstract: Long-term residential exposures to air pollution and noise are associated with increased incidence of self-reported hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
101
9
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 23 publications
8
101
9
4
Order By: Relevance
“…In one cohort study, stroke incidence was related to road traffic noise exposure 3. Moreover, several longitudinal studies indicated that exposure to transportation noise was related to obesity,4 5 diabetes6–8 and hypertension,9 which are independent risk factors of cardiovascular disease. The WHO systematic review concluded that not enough studies of good quality are available on cardiovascular and metabolic effects of transportation noise, but that the plausibility of an association calls for further and improved research, particularly studies of longitudinal design.…”
Section: Introductionmentioning
confidence: 99%
“…In one cohort study, stroke incidence was related to road traffic noise exposure 3. Moreover, several longitudinal studies indicated that exposure to transportation noise was related to obesity,4 5 diabetes6–8 and hypertension,9 which are independent risk factors of cardiovascular disease. The WHO systematic review concluded that not enough studies of good quality are available on cardiovascular and metabolic effects of transportation noise, but that the plausibility of an association calls for further and improved research, particularly studies of longitudinal design.…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure (BP) ranked the first leading risk factor for cardiovascular morbidity and mortality . In the past several years, a growing body of epidemiological studies has examined whether long‐term exposures to ambient fine particulate matter (with an aerodynamic diameter ≤2.5 μm; PM 2.5 ) pollution increase the risk of hypertension, but the findings are inconsistent . The inconsistent results may be attributable to the heterogeneity in particulate matter sizes or constituents between geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent results may be attributable to the heterogeneity in particulate matter sizes or constituents between geographic regions. Furthermore, most research was conducted in European countries and the United States, where air pollutant concentrations were low compared with China …”
Section: Introductionmentioning
confidence: 99%
“…Deaths from cardiovascular causes account for more than two thirds of the premature deaths attributable to ambient PM 2.5 air pollution 2. Increasing amounts of data suggest exposure to PM 2.5 increases the risk of cardiovascular deaths and diseases in the short and long terms 6, 7, 8, 9, 10. It also has been suggested that the long‐term effects of PM 2.5 have a greater impact on cardiovascular mortality than the short‐term effects 4, 5…”
mentioning
confidence: 99%